Livestock Farmer’s Commitment to Children’s Education: A PLS-SEM Analysis Study in Banyumas Regency - Cahyo, Danang Nur; Muatip, Krismiwati; Wakhidati, Yusmi Nur; Sugiarto, Mochamad; Safitri, Lis (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2025)
Education is the most powerful weapon and is the key to success. The livestock farmers' children's education is very important and related to the role of education in increasing knowledge, skill, and attitude, which improves the welfare of the farmer's family. Therefore, improving the farmers' commitment to children's education and the factors affected by it is necessary. Based on the previous statement, this study aimed to reveal the factors influencing farmers' commitment to children's education. This study was conducted in the Baturraden, Sumbang, Kembaran, and Sokaraja Subdistricts, Banyumas Regency, from January to February 2023, using a cross-sectional survey approach. A total of 525 livestock farmers were recorded as respondents. The data obtained were Structural Equational Modeling Partial Least Square (SEM-PLS) analyzed utilizing the SmartPLS 4 software. The results of this study showed that the increase in farmers' financial condition, children's desires, interests, and motivation could increase farmers' commitment to children's education. The farmers’ knowledge of education services variables did not affect the farmers’ commitment. Farmers’ financial conditions could indirectly affect farmers’ commitment through interests and motivation. A similar condition also occurred in farmers' children’s desire and knowledge of education services. It could be concluded from this study that improving farmers' financial condition followed by intense government educational services information dissemination could improve farmers' commitment to children's education, which would enhance children's academic level in rural areas of Indonesia.